TINJAUAN PUSTAKA: TANTANGAN DAN IMPLEMENTASI PEMBAYARAN JASA KESEHATAN DALAM SISTEM JAMINAN KESEHATAN NASIONAL (JKN) - Ayu Rindwitia indah Peanasari; Vip Paramarta (RADJA PUBLIKA, 2025)
This study aims to examine the challenges and implementation of medical service payments within the National Health Insurance (JKN) system in Indonesia through a literature review. The implementation of JKN demonstrates significant efforts to strengthen healthcare governance, including through the implementation of INA-CBGs-based payment mechanisms, the use of the Mobile JKN application, and strengthening the membership system. However, the literature review reveals that various challenges remain, such as barriers to socialization in certain regions, limitations in the usability of digital applications, the potential for fraud in the claims system, inefficiencies in drug planning and procurement, and issues with the sustainability of membership and the implementation of the tiered referral system. These findings confirm that the effectiveness of medical service payments within JKN is determined not only by the claims mechanism but also by social, technological, regulatory, and healthcare governance factors. Therefore, strong synergy is needed between the government, BPJS Kesehatan (Social Security Agency for Health), healthcare facilities, medical personnel, and the community to ensure the achievement of JKN's primary objectives, namely equitable access and sustainable improvement of healthcare quality.